Delineating the Spread and Prevalence of SARS-CoV-2 Omicron Sublineages (BA.1–BA.5) and Deltacron Using Wastewater in the Western Cape, South Africa . (26th August 2022) - Johnson, Rabia; Mangwana, Noluxabiso; Sharma, Jyoti R; Muller, Christo J F; Malemela, Kholofelo; Mashau, Funanani; Dias, Stephanie; Ramharack, Pritika; Kinnear, Craig; Glanzmann, Brigitte; Viraragavan, Amsha; Louw, Johan; et al.
Abstract: This study was one of the first to detect Omicron sublineages BA.4 and BA.5 in wastewater from South Africa. Spearman rank correlation analysis confirmed a strong positive correlation between severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) viral RNA in wastewater samples and clinical cases ( r = 0.7749, P < .0001). SARS-CoV-2 viral load detected in wastewater, resulting from the Delta-driven third wave, was significantly higher than during the Omicron-driven fourth wave. Whole-genome sequencing confirmed presence of Omicron lineage defining mutations in wastewater with the first occurrence reported 23 November 2021 (BA.1 predominant). The variant spread rapidly, with prevalence of Omicron-positive wastewater samples rising to >80% by 10 January 2022 with BA.2 as the predominant sublineage by 10 March 2022, whilst on 18 April 2022 BA.4 and BA.5 were detected in selected wastewater sites. These findings demonstrate the value of wastewater-based epidemiology to monitor the spatiotemporal spread and potential origin of new Omicron sublineages. Abstract : This was one of the first studies to detect Omicron sublineages in wastewater from South- Africa. BA.1 was detected in wastewater on 23 November 2021, followed by BA.2 on 10 March 2022, whilst on 18 April 2022 BA.4 and BA.5 were detected in selected sites.